Institutional Performance and Social Impact: A Case Study of Drug and Food Regulatory Agency in Safeguarding Public Health in South Sumatra - Jafarudin, Muhamad (Jurnal Sains Sosio Humaniora, 2025)
This study evaluates the institutional performance and social impact of the National Center for Drug and Food Control (BBPOM) in Palembang, focusing on its role in public health governance within South Sumatra province in 2024. This research investigates how regulatory agencies function as critical social actors in safeguarding public welfare. Using a quantitative descriptive research design, the study analyzes key performance indicators, budget realization, and efficiency data from January to December 2024. The results reveal that BBPOM Palembang exceeded its performance targets, achieving 100.84% of its objectives and maintaining a budget efficiency rate of 98.84%. The agency successfully tested 1,471 drug samples (100.48% of the target) and 584 food samples (101.92% of the target), while reaching 13,353 community members through health education programs. These findings demonstrate BBPOM’s institutional effectiveness in translating national health policies into local outcomes, with a high public satisfaction rate of 95.9%. However, challenges remain in ensuring food safety compliance (90.58% vs. the 91.00% target) and improving the efficiency of criminal case handling (87.14%). This study provides valuable insights into regulatory governance in emerging economies, highlighting the role of public institutions in upholding community health rights and fostering social welfare. The research contributes empirical evidence to support policy improvements in pharmaceutical and food safety governance, emphasizing the relationship between institutional performance, social accountability, and community well-being.